Comparison of autologous hematopoietic cell transplantation, matched sibling donor hematopoietic cell transplantation, and chemotherapy in patients with favorable- and intermediate-risk acute myeloid leukemia - Wang, Mingyang; Chen, Shulian; Zhang, Qiuqiu; Yuan, Linyu; Wang, Xue; Zhang, Junshi; Zhang, Xiaoyu; Cao, Yigeng; Li, Dongmei; Lu, Xinxiao; Wang, Meijiao; Jiang, Xiaosi; et al. (Frontiers in Immunology, 2025)
IntroductionHematopoietic stem cell transplantation (HSCT) and chemotherapy are considered potentially curative options for post-remission therapy in acute myeloid leukemia (AML). However, the comparative effectiveness of these approaches in favorable- and intermediate-risk AML remains unclear and requires further investigation.MethodsIn this retrospective study, 111 patients diagnosed with de novo favorable- and intermediate-risk AML, categorized according to the ELN 2022 guidelines, were investigated to compare outcomes following autologous HSCT (auto-HSCT), matched sibling donor HSCT (MSD-HSCT), and chemotherapy. Through propensity score matching for disease status before HSCT, 42 cases in first complete remission were selected for each of the auto-HSCT group and the MSD-HSCT group. Additionally, 27 cases in the chemotherapy group, excluding patients with early relapse or death, were included for comparison.ResultsIn the overall population, the 3-year overall survival (OS) rates were 85.7%, 83.1%, and 70.4% (p = 0.043), while the disease-free survival (DFS) rates were 78.6%, 83.2%, and 57.1% (p = 0.002) in the auto-HSCT, MSD-HSCT, and chemotherapy groups, respectively. Notably, both auto-HSCT and MSD-HSCT demonstrated significantly improved DFS compared to chemotherapy in patients with favorable-risk AML. Multivariate analysis further revealed that chemotherapy was significantly associated with inferior DFS compared to auto-HSCT (HR=2.82; 95% CI, 1.26–6.32, p=0.012), while DFS was similar between the MSD-HSCT and auto-HSCT groups (HR=0.80; 95% CI, 0.31–2.09, p=0.645).DiscussionThe findings suggested the advantages of both MSD-HSCT and auto-HSCT over chemotherapy as post-remission therapy for AML patients with favorable and intermediate risk. Further research is needed to support these conclusions.